2022
DOI: 10.1002/btm2.10386
|View full text |Cite|
|
Sign up to set email alerts
|

Cell loaded hydrogel containing Ag‐doped bioactive glass–ceramic nanoparticles as skin substitute: Antibacterial properties, immune response, and scarless cutaneous wound regeneration

Abstract: An ideal tissue-engineered dermal substitute should possess angiogenesis potential to promote wound healing, antibacterial activity to relieve the bacterial burden on skin, as well as sufficient porosity for air and moisture exchange. In light of this, a glass-ceramic (GC) has been incorporated into chitosan and gelatin electrospun nanofibers (240-360 nm), which MEFs were loaded on it for healing acceleration. The GC was doped with silver to improve the antibacterial activity. The bioactive nanofibrous scaffol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…can be integrated into their flexible glass network to improve the biological properties of BG such as angiogenesis, osteogenesis, and antibacterial effects. 25,27,30,33,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] The biological responses to ionic dissolution products of BGs are schemed in Figure 2. 26 Generally, the metallic ions are important components of many enzymes and function as cofactors that stimulate metabolic reactions associated with cell signaling pathways during tissue regeneration.…”
Section: Ion-mediated Biological Functionalitymentioning
confidence: 99%
“…can be integrated into their flexible glass network to improve the biological properties of BG such as angiogenesis, osteogenesis, and antibacterial effects. 25,27,30,33,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] The biological responses to ionic dissolution products of BGs are schemed in Figure 2. 26 Generally, the metallic ions are important components of many enzymes and function as cofactors that stimulate metabolic reactions associated with cell signaling pathways during tissue regeneration.…”
Section: Ion-mediated Biological Functionalitymentioning
confidence: 99%
“…Sharifi et al [ 23 ] reported the use of silver, obtained the bioactive glass 45S5-Ag and incorporated it into scaffolds based on gelatin, chitosan and polyethylene oxide. Biological tests showed antibacterial activity against gram-positive and gram-negative species for samples containing BG-Ag (~36 nm particles), in addition to an improved regenerative response.…”
Section: Composites Of Gelatin/bg For Tissue Engineeringmentioning
confidence: 99%
“… Images obtained by scanning electron microscopy (SEM) of the scaffolds used for 24 h culture of fibroblasts: chitosan, gelatin and PEO matrix ( a ), polymeric matrix modified by BG ( b ) and polymeric matrix combined with BG-Ag ( c ). Adapted from Sharifi et al [ 23 ]. …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations